Clinical characteristics of COVID-19 in hospitalized children during the Omicron variant predominant period. Issue 11 (November 2022) - Shoji, Kensuke; Akiyama, Takayuki; Tsuzuki, Shinya; Matsunaga, Nobuaki; Asai, Yusuke; Suzuki, Setsuko; Iwamoto, Noriko; Funaki, Takanori; Ohmagari, Norio
Abstract: Introduction: Information regarding the clinical manifestations and outcomes of coronavirus disease 2019 (COVID-19) in children under the Omicron variant predominant period is still limited. Methods: A nationwide retrospective cohort study was conducted. Pediatric COVID-19 patients (<18 years of age) hospitalized between August 1, 2021 and March 31, 2022 were enrolled. Epidemiological and clinical characteristics between the Delta variant predominant period (August 1 to December 31, 2021) and the Omicron variant predominant period (January 1 to March 31, 2022) were compared. Results: During the study period, 458 cases in the Delta predominant period and 389 cases in the Omicron predominant period were identified. Median age was younger (6.0 vs. 8.0 years, P  = 0.004) and underlying diseases were more common (n = 65, 16.7% vs. n = 53, 11.6%) in the Omicron predominant period than those in the Delta variant predominant era. For clinical manifestations, fever ≥38.0 °C at 2 to <13 years old, sore throat at ≥ 13 years, and seizures at 2 to <13 years old were more commonly observed, and dysgeusia and olfactory dysfunction at ≥ 6 years old were less commonly observed in the Omicron variant predominant period. The number of patients requiring noninvasive oxygen support was higher in the Omicron predominant period than that in the Delta predominant period; however, intensive care unit admission rates were similar and no patients died in both periods. Conclusions: In the Omicron variant predominant period, more pediatric COVID-19 patients experienced fever and seizures, although the overall outcomes were still favorable.